Water Accommodation on Ice and Organic Surfaces: Insights from Environmental Molecular Beam Experiments - Kong, Xiangrui; Thomson, Erik S; Papagiannakopoulos, Panos; Johansson, Sofia M.; Pettersson, Jan B. C. (The Journal of Physical Chemistry Part B, 2014)
Water uptake on aerosol and cloud particles in the atmosphere modifies their chemistry and microphysics with important implications for climate on Earth. Here, we apply an environmental molecular beam (EMB) method to characterize water accommodation on ice and organic surfaces. The adsorption of surface-active compounds including short-chain alcohols, nitric acid, and acetic acid significantly affects accommodation of D2O on ice. n-Hexanol and n-butanol adlayers reduce water uptake by facilitating rapid desorption and function as inefficient barriers for accommodation as well as desorption of water, while the effect of adsorbed methanol is small. Water accommodation is close to unity on nitric-acid- and acetic-acid-covered ice, and accommodation is significantly more efficient than that on the bare ice surface. Water uptake is inefficient on solid alcohols and acetic acid but strongly enhanced on liquid phases including a quasi-liquid layer on solid n-butanol. The EMB method provides unique information on accommodation and rapid kinetics on volatile surfaces, and these studies suggest that adsorbed organic and acidic compounds need to be taken into account when describing water at environmental interfaces.
Keywords: NITRIC-ACID; CONDENSATION COEFFICIENT; CHAIN MOLECULES; DEPOSITION; COEFFICIENT; DYNAMICS SIMULATIONS; COLLISION DYNAMICS; MASS; ACCOMMODATION; CIRRUS CLOUDS; METHANOL FILM; ACETIC-ACID